Tailoring the adhesion of electrophoretic chitosan/bioactive glass coatings by the combined surface pre-treatments of Ti substrates - Kowalczyk, Agnieszka; Sotniczuk, Agata; Kuczyńska-Zemła, Donata; Pura, Jarosław; Xu, Zhiyan; Boccaccini, Aldo R.; Garbacz, Halina (Surface & Coatings Technology, 2024)
Composite chitosan/bioactive glass coatings developed by electrophoretic deposition (EPD) attract researchers' attention owing to their advantageous effect on the biological and corrosion responses of commonly used biomedical materials. However, fabricating a uniform coating with satisfactory adhesion to the biomaterials substrate is challenging, because chitosan and bioglass particles having different mobilities during the EPD process. Typically, attempts are made to improve adhesion by manipulating the EPD parameters. This work presents an alternative approach that involves combined mechanical and chemical pre-treatments of the Ti substrate. The surface pre-treatment procedure included shot peening and the following variants of acid etching: (i) HF etching, (ii) NaOH etching, and (iii) HF and NaOH etching. Shot peening followed by etching in HF and NaOH significantly improved the adhesion of the EPD coating. It was found that this effect was due to the development of a highly hydrophilic surface with micro- and nano-scale roughness.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Bioactive glass; Chitosan; Electrophoretic deposition; Surface topography; Titanium